Experiências de alunas e alunos LGBTQs e identidade de gênero na escola - Santos, Samuel Rodrigues dos (2017)
This master’s thesis had as its objective to gather and analyze narratives of LGBTQ students or former students in elementary school and high school. I tried to answer the following research question: How do LGBTQ students live their experiences in the school spaces? The theoretical and methodological path of this research was the Narrative Inquiry according to Clandinin and Connelly (2000, 2011, 2015) because I understand that we can comprehend the lived experiences better by narrating them. Clandinin and Connelly (2000, 2011, 2015) use the concept of experience by Dewey (1938, 1979). The theoretical basis for this research was the queer theory, according to the authors Butler (2003), Louro (2001, 2014), Miskolci (2012) and Spargo (1999), and the theory of gender identity, according to the authors Jesus, Carbonieri e Nigro (2017), Moita Lopes (2009), Bento (2015) and Benfatti (2013). The four research participants were me, I identify myself as a gay man, Glendha, who identifies herself as a transgender woman, Valentina who identifies herself as a lesbian woman, and Ariel, who identifies himself as a gay man. During the research, we had five meetings face to face and several other moments over WhatsApp in which we, as research participants, shared our stories lived in school. I analyzed our stories through the perspective of meaning composition, according to Ely, Vinz, Downing e Anzul (2005), writing dialogues in the form of seven theater scenes that touched seven different themes noticed on the participants’ stories. The themes of the scenes were: LGBTQ students’ loneliness, the blame, the body, the bullying in school, LGBTQ students in state and private schools, the family members and religion. Finally, it was possible to notice that the lived and told experiences in this research were about prejudice and disrespect against LGBTQ people. It was also possible to get to know the ways and strategies used by these students to deal with difficult situations lived in school almost daily.